The Molecular Phylogeny of the New Zealand Endemic Genus Hadramphus and the Revival of the Genus Karocolens - Emily D. Fountain; Robert H. Cruickshank; Adrian M. Paterson (Diversity, 2018)
The delineation of species is important to the fields of evolution, ecology and conservation. The use of only a single line of evidence, e.g., morphology or a single gene sequence, may underestimate or overestimate the level of diversity within a taxon. This problem often occurs when organisms are morphologically similar but genetically different, i.e., for cryptic species. The Hadramphus genus contains four endangered, morphologically similar species of weevils, each endemic to a specific New Zealand region (Hadramphus spinipennis Chatham Islands, H. stilbocarpae Fiordland, H. tuberculatus McKenzie Country, H. pittospori Poor Knights Islands). The systematic relationships among these species are unclear. We used samples from these species and a closely related genus, Lyperobius huttoni, to obtain data from the mitochondrial gene cytochrome c oxidase subunit I and the nuclear gene internal transcribe spacer 2. In addition to the multi-locus coalescent approach, we modelled morphological characteristics combined with the genetic data. We found that H. spinipennis, H. tuberculatus and H. stilbocarpae were a closely related clade. Despite a strong morphological similarity, Hadramphus pittospori was found to be genetically distinct from the other Hadramphus species, which supports the resurrection of the monotypic genus Karocolens for this species.